2018
DOI: 10.3389/fcimb.2018.00196
|View full text |Cite
|
Sign up to set email alerts
|

Development of a High-Throughput ex-Vivo Burn Wound Model Using Porcine Skin, and Its Application to Evaluate New Approaches to Control Wound Infection

Abstract: Biofilm formation in wounds is considered a major barrier to successful treatment, and has been associated with the transition of wounds to a chronic non-healing state. Here, we present a novel laboratory model of wound biofilm formation using ex-vivo porcine skin and a custom burn wound array device. The model supports high-throughput studies of biofilm formation and is compatible with a range of established methods for monitoring bacterial growth, biofilm formation, and gene expression. We demonstrate the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 47 publications
(99 reference statements)
1
25
0
2
Order By: Relevance
“…In addition, we showed that the six-phage preparation can efficiently prevent the formation of a biofilm produced by E28 in vitro and significantly reduce an existing biofilm as reported by others [ 84 , 85 , 86 , 87 ]. Biofilms are a problem especially in the pipe systems of drinking troughs, as they are difficult to eliminate by disinfectants or cleaning [ 88 ].…”
Section: Discussionsupporting
confidence: 79%
“…In addition, we showed that the six-phage preparation can efficiently prevent the formation of a biofilm produced by E28 in vitro and significantly reduce an existing biofilm as reported by others [ 84 , 85 , 86 , 87 ]. Biofilms are a problem especially in the pipe systems of drinking troughs, as they are difficult to eliminate by disinfectants or cleaning [ 88 ].…”
Section: Discussionsupporting
confidence: 79%
“…Further, the porcine immune system is highly similar to the human immune system, making it well-suited to study host-microbial interactions (Ganesh et al, 2015;Jensen et al, 2017). Alves, D. R. et al (2018) employed the use of an ex vivo porcine skin model as a substrate to study S. aureus biofilm formation and virulence gene expression in thermally induced wounds. In this model, a burn wound array device (BWAD) is used to create partial-thickness thermal injuries, following which the skin is excised and employed as a substrate for microbial inoculation.…”
Section: Ex Vivo Systemsmentioning
confidence: 99%
“…In another work, another ex vivo porcine skin model of wound infection was used for monitoring bacterial growth, biofilm formation, and gene expression [123]. This model tested phage control of S. aureus biofilm formation and the population density-dependent regulation of virulence gene expression during S. aureus growth.…”
Section: Phage Therapy For Chronic Wound Healing-ex Vivo and Animal Imentioning
confidence: 99%